Hybrid substrate
By using a composite layer structure of polyaryl sulfide resin and thermoplastic resin on the printed circuit board, the transmission loss and material inhomogeneity of the high-frequency circuit board are solved, and the low dielectric constant and high adhesion are achieved, which are suitable for high-frequency communications and vehicle-mounted millimeter wave radars.
Patent Information
- Application Number
- JP2023122363
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
Existing high-frequency circuit board materials have problems such as large transmission losses, material unevenness, poor adhesion, and insufficient high temperature resistance, which is difficult to meet the needs of high-frequency communications and vehicle-mounted millimeter-wave radar.
Using a low-dielectric material layer composed of polyaryl sulfide resin (PAS) and other thermoplastic resins, the adhesion and heat resistance are improved, and the dielectric constant and loss are reduced by forming a composite layer structure of continuous and dispersed phases on the printed circuit board.
It achieves low dielectric constant, low loss, excellent adhesion and high temperature resistance, and is suitable for high-frequency communication and vehicle-mounted millimeter wave radar, improving the performance and reliability of the circuit board.
Smart Images

Figure 2025018559000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a high-frequency hybrid substrate in which a printed wiring board (2) having an insulating layer made of a low-dielectric material is laminated on one or both sides of a printed wiring board (1) having an insulating layer formed of an epoxy glass cloth laminate. [Background technology]
[0002] In fields such as high-speed, large-capacity communications (5G) and in-vehicle millimeter-wave radar, there is a demand for high-frequency boards made of low-dielectric materials and metal wiring that have little transmission loss even when using high frequencies. However, because low-dielectric materials are expensive, high-frequency hybrid boards have been developed that use them only in the surface antenna and high-frequency transmission sections, and use printed wiring boards (1) with insulating layers made of epoxy glass cloth laminates, a relatively inexpensive common material, for low-frequency wiring for control and power supply. Furthermore, in high-frequency hybrid boards, it is expected that there will be an increase in applications where the high-frequency wiring layer of the surface printed wiring board (2) is formed into three or more layers, thereby achieving higher functionality.
[0003] An example of technology related to high frequency hybrid substrates is cited in Reference 1. The advantage is that the connection between printed wiring board (1) and printed wiring board (2) can be manufactured with good productivity using solder or conductive paste, but the disadvantage is that the conductivity is lower than when electrical continuity is achieved using metal foil or a plating layer. In addition, because a low dielectric material based on glass cloth is used as the high frequency substrate, there is a problem of material non-uniformity caused by the glass cloth in the low dielectric layer.
[0004] In the cited document 2, a method is proposed for manufacturing a multilayer printed wiring board with excellent low warpage in an asymmetrical configuration having a printed wiring board (1) with a general-purpose insulating layer and a printed wiring board (2) with an insulating layer of a low-dielectric material, for example, by laminating a high-frequency substrate with an adhesive layer on one side of a printed wiring board with an insulating layer formed of an epoxy glass cloth laminate, which is a core layer, and forming a resin layer with the same adhesive layer alone on the opposite side. However, since it is necessary to add a resin layer with an adhesive layer to suppress warpage, there are problems such as a reduction in design freedom and a complicated process. In the cited document 3, a high-frequency hybrid substrate with excellent drilling processability is obtained by using the printed wiring board (1) as the core layer, but since the printed wiring board (2) with an insulating layer of a low-dielectric material is made of a low-dielectric material with a glass cloth base material, there is a problem of in-plane material non-uniformity.
[0005] The surface printed wiring board (2) is made of a low dielectric material and metal wiring (conductive material). As mentioned above, a low dielectric material based on glass cloth may be used as the low dielectric material. However, in this case, the non-uniformity of the insulating material due to the mesh of the glass cloth can cause variations in the electrical characteristics, and the presence of the mesh of the glass cloth can easily induce unevenness on the surface of the insulating material, so it is desirable to use a low dielectric material that does not use glass cloth.
[0006] In order to form a printed wiring board (2) made of a low dielectric material without glass cloth on the surface of a printed wiring board (1), there is a method of forming a low dielectric material layer by applying a solution of the low dielectric material and then drying and curing it. However, there are problems with the cumbersome process of drying the solvent and the deterioration of the smoothness of the surface during the drying process. For this reason, the method of attaching a film of a low dielectric material (hereinafter abbreviated as low dielectric film) to the printed wiring board (1) is preferable because it is a simple process and it is easy to obtain a smooth surface.
[0007] Known materials for low dielectric films include fluororesins, liquid crystal polymers (hereinafter sometimes referred to as "LCPs"), cyclic olefins (hereinafter sometimes referred to as "COPs"), modified polyimides (hereinafter sometimes referred to as "MPIs"), and polyarylene sulfide resins (hereinafter sometimes referred to as "PAS resins") such as polyphenylene sulfide resins (PPS). Among them, fluororesins have excellent dielectric properties, but they are expensive and have poor adhesion, making lamination and adhesion of copper wiring difficult. LCPs also have excellent dielectric properties, but they are expensive and tend to peel off in layers, making lamination of printed wiring boards (2) difficult. COPs also have poor adhesion and heat resistance. MPIs have the problem of being easily hygroscopic, resulting in poor dielectric properties under high humidity.
[0008] Low-dielectric films using polyarylene sulfide resin (PAS) have good dielectric properties and are excellent in heat resistance, flame retardancy, and low moisture absorption, making them suitable as low-dielectric materials for high-frequency hybrid substrates. However, they have issues such as insufficient adhesion to low-density copper foil and insufficient reflow resistance. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2020-174115 A [Patent Document 2] JP 2016-40797 A [Patent Document 3] Japanese Patent Application Publication No. 6-5998 Summary of the Invention [Problem to be solved by the invention]
[0010] The present invention provides a high-frequency hybrid substrate that is characterized by excellent adhesion to an insulating layer formed of an epoxy glass cloth laminate of a printed wiring board and excellent reflow resistance, by using a printed wiring board having an insulating layer made of a film (hereinafter sometimes abbreviated as PAS-based film) made of a polyarylene sulfide-based resin having a specific thermoplastic resin dispersed therein. [Means for solving the problem]
[0011] As a result of intensive research, the inventors have found that the above-mentioned problems can be solved by a high-frequency hybrid substrate in which a printed wiring board (2) having a low dielectric material layer made of a resin layer composed of a resin composition of polyarylene sulfide resin (A) and thermoplastic resin (B) other than polyarylene sulfide resin having a glass transition temperature of 200°C or more or a melting point of 230°C or more is laminated on one or both sides of a printed wiring board (1) having an insulating layer formed of an epoxy glass cloth laminate, and have thus completed the present invention. That is, the present invention relates to the following (1) to (10).
[0012] (1) A high-frequency hybrid substrate in which a printed wiring board (2) having an insulating layer made of a low-dielectric material is laminated on one or both sides of a printed wiring board (1) having an insulating layer formed of an epoxy glass cloth laminate, A high frequency hybrid substrate, characterized in that the low dielectric material is made of a resin composition of a polyarylene sulfide resin (A) and a thermoplastic resin (B) other than a polyarylene sulfide resin having a glass transition temperature of 200°C or higher or a melting point of 230°C or higher. (2) The high frequency hybrid substrate according to 1, wherein the blending ratio of the thermoplastic resin (B) other than the polyarylene sulfide-based resin having a glass transition temperature of 200°C or higher or a melting point of 230°C or higher is in the range of 3 to 49 mass% relative to 100 mass% of the total amount of the polyarylene sulfide-based resin (A) and the thermoplastic resin (B) other than the polyarylene sulfide-based resin having a glass transition temperature of 200°C or higher or a melting point of 230°C or higher. (3) The high frequency hybrid substrate according to 1 or 2, wherein the thermoplastic resin (B) other than a polyarylene sulfide resin having a glass transition temperature of 200°C or higher or a melting point of 230°C or higher is a dispersed phase having an average dispersed diameter of 5 μm or less. (4) The high frequency hybrid substrate according to any one of 1 to 3, wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is at least one selected from the group consisting of polyphenylene ether resin, polyethersulfone resin, polyphenylsulfone resin, polyetherimide resin, polysulfone resin, and fluorine-based resin. (5) The high frequency hybrid substrate according to any one of 1 to 4, wherein the low dielectric material has a dielectric constant of 3.4 or less. (6) The high frequency hybrid substrate according to any one of 1 to 5, further comprising a modified elastomer (C) having a reactive group added to a resin composition of a low dielectric material. (7) The high frequency hybrid substrate according to 6, wherein the modified elastomer (C) is made of an olefin polymer having at least a functional group selected from the group consisting of an epoxy group and an acid anhydride group. (8) The high frequency hybrid substrate according to 6 or 7, wherein the blending ratio of the modified elastomer (C) is 1 to 15 mass% relative to 100 mass% in total of the polyarylene sulfide resin (A), the thermoplastic resin (B), and the modified elastomer (C). (9) The high frequency hybrid substrate according to any one of 6 to 8, wherein the modified elastomer (C) has an α-olefin content of 50 to 95% by mass based on the total mass of the modified elastomer. (10) The high frequency hybrid substrate according to any one of (6) to (9), further comprising 0.01 to 5 mass % of a silane coupling agent (D) having at least one functional group selected from an epoxy group, an amino group, and an isocyanate group. (11) A millimeter wave radar and an antenna using the high frequency hybrid substrate according to any one of 1 to 10. This is regarding. Effect of the Invention
[0013] According to the present invention, a high frequency hybrid substrate can be obtained in which the low dielectric material of the surface layer has low dielectric tangent, flame retardancy, low water absorption, high adhesion to a metal layer, high adhesion to an epoxy glass cloth layer, and excellent reflow resistance. [Brief description of the drawings]
[0014] [Figure 1] This is a cross-sectional view of a high-frequency hybrid substrate in which a printed wiring board (2) with an insulating layer made of a low-dielectric material is laminated on one side of a printed wiring board (1) with an insulating layer formed of an epoxy glass cloth laminate. [Diagram 2] This is a cross-sectional view of a high-frequency hybrid substrate in which a printed wiring board (2) with an insulating layer made of a low-dielectric material is laminated on both sides of a printed wiring board (1) with an insulating layer formed of an epoxy glass cloth laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, an embodiment of the present invention will be described in detail.
[0016] [Printed wiring board with an insulating layer formed from an epoxy glass cloth laminate (1)] The epoxy glass cloth laminate used in the present invention is a plate-shaped insulating material obtained by subjecting prepregs, which are composite materials obtained by semi-curing glass cloth impregnated with epoxy resin, to a heat curing treatment, either alone or after laminating them to a desired thickness. This material is widely used because it is both flame retardant and low conductive, but the low conductivity is insufficient for use in high-frequency applications such as 5G communications and millimeter-wave antennas. A known method can be used to manufacture a printed wiring board (1) using the insulating material. For example, a copper foil is attached to one or both sides at the same time as the heat curing treatment, and then a wiring pattern is formed by a resist etching method, and then a single-sided or double-sided printed wiring board (1) can be obtained by forming wiring in the thickness direction by drilling holes with a drill or laser and imparting conductivity to the holes by via plating, etc. Furthermore, the printed wiring board (1) used in the present invention can also be obtained by multi-layering the single-sided or double-sided printed wiring board (1) by heat treatment, using a prepreg, which is a composite material obtained by semi-curing glass cloth impregnated with epoxy resin, as an adhesive layer. The wiring in the thickness direction may be formed by drilling through holes after manufacturing the multi-layered printed wiring board (1) and then conducting the through holes with plating or conductive resin. As the insulating material for the printed wiring board (1), the epoxy glass cloth laminate is a general-purpose material that combines flame retardancy and low conductivity, and is most suitable because of its good electrical insulation stability and flatness. However, if it is suitable for the application, a printed wiring board made of a glass composite board, paper epoxy board, paper phenol board, etc. may be used to reduce costs.
[0017] [Printed wiring boards with low dielectric material as an insulating layer (2)] The method for producing the copper-clad low dielectric material used in the present invention may be to copper-clad the low dielectric material alone, or to copper-clad the outermost layer after or simultaneously with attaching the low dielectric material to the printed wiring board (1). The copper cladding method for the low dielectric material may be thermal lamination, attachment with an adhesive or a bonding sheet, or a metal layer may be formed by a plating method such as sputter plating. When attaching copper foil, it is preferable that the surface of the copper foil is smooth in order to reduce transmission loss at high frequencies. For example, Rz is preferably 3 μm or less, but a copper foil with suitable unevenness can be selected depending on the application. The plating method has a higher processing cost than attaching copper foil, but has the advantage that the interface between the insulating layer and the metal layer is smooth, so it is suitable when there is a demand for reducing transmission loss at high frequencies.
[0018] By forming a wiring pattern on the copper-clad low dielectric material using a known method, a printed wiring board (2) with the low dielectric material as an insulating layer can be obtained. The wiring formation method is not particularly limited, and examples include a method of forming wiring by etching the copper-clad low dielectric material, a method of directly forming a metal layer on the required parts of the low dielectric material, and a combination of both methods. Wiring can be formed by a subtractive method, a semi-additive method, a full-additive method, etc.
[0019] [Low dielectric resin composition] The resin composition of the low dielectric material used in the printed wiring board (2) with the insulating layer made of a low dielectric material is mainly composed of a polyarylene sulfide resin (A) and a thermoplastic resin (B) other than the polyarylene sulfide resin (A) having a glass transition temperature of 200°C or more or a melting point of 230°C or more. In this case, the resin composition has a continuous phase and a dispersed phase, the continuous phase contains the polyarylene sulfide resin (A), and the dispersed phase contains the thermoplastic resin (B). In addition, the main component in the present invention means that the polyarylene sulfide resin accounts for 51% by mass or more when the entire resin composition is taken as 100% by mass. By including the thermoplastic resin (B) in the dispersed layer, the adhesion to the metal layer or the epoxy glass cloth laminate can be improved compared to using the PAS resin alone. In particular, by including the thermoplastic resin (B) which is an amorphous resin or a fluorine resin, the unevenness-following ability is improved, and stress is less likely to concentrate due to high flexibility, so that the effect of improving the adhesion to the metal layer or the epoxy glass cloth laminate is high.
[0020] The average dispersion diameter of the dispersed phase is 5 μm or less, preferably 3 μm or less, more preferably 0.5 to 3 μm. When the average dispersion diameter of the dispersed phase is 5 μm or less, a uniform film can be obtained. In the present invention, the "average dispersion diameter of the dispersed phase" is a value measured by the method described in the Examples.
[0021] [Polyarylene sulfide resin (A)] The polyarylene sulfide resin (A) is the main component of the resin composition, and is a component having the function of imparting excellent heat resistance, chemical resistance, and dielectric properties to the insulating layer.
[0022] The PAS resin (A) is a polymer containing a structure in which an aromatic ring and a sulfur atom are bonded (specifically, a structure represented by the following formula (1)) as a repeating unit.
[0023] [ka] (In the above formula, R 1each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethoxy group, and each n independently represents an integer of 1 to 4.
[0024] Here, R in the structure represented by formula (1) 1 It is preferable that R is a hydrogen atom. This structure can further increase the mechanical strength of the PAS resin (A). 1 are hydrogen atoms, includes a structure represented by the following formula (2) (i.e., a structure in which a sulfur atom is bonded to an aromatic ring at a para position) and a structure represented by the following formula (3) (i.e., a structure in which a sulfur atom is bonded to an aromatic ring at a meta position).
[0025] [ka] Among these, the structure represented by formula (1) is preferably a structure represented by formula (2). If the PAS resin (A) has the structure represented by formula (2), the heat resistance and crystallinity can be further improved.
[0026] Furthermore, the PAS resin (A) may contain not only the structure represented by the above formula (1) but also structures represented by the following formulas (4) to (7) as repeating units.
[0027] [ka]
[0028] The structures represented by the formulae (4) to (7) are preferably contained in an amount of 30 mol % or less, more preferably 10 mol % or less, of all repeating units constituting the PAS resin (A), which can further increase the heat resistance and mechanical strength of the PAS resin (A). The bonding pattern of the structures represented by formulas (4) to (7) may be either random or block.
[0029] The PAS resin (A) may contain, as a repeating unit, a trifunctional structure represented by the following formula (8), a naphthyl sulfide structure, or the like, in its molecular structure.
[0030] [ka]
[0031] The structure represented by formula (8), naphthyl sulfide structure, etc. are preferably contained in an amount of 1 mol % or less, and more preferably substantially absent, in all repeating units constituting the PAS resin (A). With such a structure, the content of chlorine atoms in the PAS resin (A) can be reduced. The properties of the PAS resin (A) are not particularly limited as long as they do not impair the effects of the present invention. However, the melt viscosity (V6) at 300°C is preferably 100 to 2000 Pa s, and more preferably 120 to 1600 Pa s in order to achieve a good balance between fluidity and mechanical strength.
[0032] Furthermore, it is particularly preferred that the PAS resin (A) has a peak in the molecular weight range of 25,000 to 40,000 when measured by gel permeation chromatography (GPC), has a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) in the range of 5 to 10, and has a non-Newtonian index in the range of 0.9 to 1.3. By using such a PAS resin (A), the chlorine atom content in the PAS resin (A) itself can be reduced to the range of 500 to 2,000 ppm without reducing the mechanical strength of the film, facilitating application to halogen-free electronic and electrical component applications.
[0033] In this specification, the weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) are values measured by gel permeation chromatography (GPC). The measurement conditions for GPC are as follows: [Measurement conditions for gel permeation chromatography] Equipment: Ultra-high temperature polymer molecular weight distribution measuring device (SSC-7000 manufactured by Senshu Scientific Co., Ltd.) Column: UT-805L (Showa Denko) Column temperature: 210℃ Solvent: 1-chloronaphthalene Measurement method: UV detector (360 nm) calibrated with six types of monodisperse polystyrene. The molecular weight distribution and peak molecular weight are measured using the method.
[0034] The method for producing the PAS resin (A) is not particularly limited, but examples thereof include 1) a method in which a dihalogenoaromatic compound, if necessary a polyhalogenoaromatic compound or other copolymerization component is added in the presence of sulfur and sodium carbonate, and polymerized, 2) a method in which a dihalogenoaromatic compound, if necessary a polyhalogenoaromatic compound or other copolymerization component is added in the presence of a sulfidizing agent or the like in a polar solvent, and polymerized, 3) a method in which p-chlorothiophenol, if necessary another copolymerization component is added, and self-condensed, etc. Among these production methods, the above method 2) is versatile and preferred. During the reaction, an alkali metal salt of a carboxylic acid or a sulfonic acid, or an alkali hydroxide may be added to adjust the degree of polymerization.
[0035] Among the above-mentioned method 2), the following method 2-1) or method 2-2) is particularly preferred. In method 2-1), a water-containing sulfidizing agent is introduced into a mixture containing a heated organic polar solvent and a dihalogeno aromatic compound at a rate at which water can be removed from the reaction mixture, and the dihalogeno aromatic compound and the sulfidizing agent are added, if necessary, to a polyhalogeno aromatic compound in the organic polar solvent, and the water content in the reaction system is controlled to within a range of 0.02 to 0.5 moles per mole of the organic polar solvent to produce a PAS resin (A) (see JP-A-07-228699). In the method of 2-2), a dihalogeno aromatic compound and, if necessary, a polyhalogeno aromatic compound or other copolymerization component are added in the presence of a solid alkali metal sulfide and an aprotic polar organic solvent, and an alkali metal hydrosulfide and an organic acid alkali metal salt are reacted with each other by controlling the amount of the organic acid alkali metal salt to within a range of 0.01 to 0.9 mol per mol of the sulfur source and controlling the amount of water in the reaction system to within a range of 0.02 mol or less per mol of the aprotic polar organic solvent, thereby producing a PAS resin (A) (see WO2010 / 058713 pamphlet).
[0036] Specific examples of the dihalogeno aromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalodiphenyl sulfoxide, 4,4'-dihalodiphenyl sulfide, and the above compounds each having an alkyl group having 1 to 18 carbon atoms on the aromatic ring. Examples of the polyhalogeno aromatic compounds include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, and 1,4,6-trihalonaphthalene. The halogen atoms contained in the above compounds are preferably chlorine atoms or bromine atoms.
[0037] The reaction mixture containing the PAS resin (A) obtained by the polymerization step can be post-treated by a known method, which is not particularly limited, and may, for example, be any of the following methods (1) to (5):
[0038] In the method (1), after the polymerization reaction is completed, the solvent is first distilled off under reduced pressure or normal pressure, either directly from the reaction mixture or after addition of an acid or a base, and then the solid matter remaining after the solvent distillation is washed once or twice or more times with a solvent such as water, the reaction solvent (or an organic solvent having an equivalent solubility to the low molecular weight polymer), acetone, methyl ethyl ketone, or an alcohol, and then neutralized, washed with water, filtered, and dried. In the method (2), after the polymerization reaction is completed, a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, or aliphatic hydrocarbons (a solvent that is soluble in the polymerization solvent used and is a poor solvent for at least the PAS resin (A)) is added to the reaction mixture as a precipitating agent to precipitate solid products such as the PAS resin (A) and inorganic salts, which are then filtered, washed, and dried. In the method (3), after the polymerization reaction is completed, a reaction solvent (or an organic solvent having an equivalent solubility for the low molecular weight polymer) is added to the reaction mixture and stirred, and then the mixture is filtered to remove the low molecular weight polymer. The mixture is then washed once or twice or more times with a solvent such as water, acetone, methyl ethyl ketone, or alcohols, and then neutralized, washed with water, filtered, and dried. In the method (4), after the polymerization reaction is completed, water is added to the reaction mixture, which is then washed with water, filtered, and if necessary, acid is added during the water washing step for acid treatment, and the mixture is then dried. In the method (5), after the polymerization reaction is completed, the reaction mixture is filtered, washed once or more times with the reaction solvent as required, further washed with water, filtered and dried.
[0039] Examples of acids that can be used in the above method (4) include organic acids such as saturated fatty acids, such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, and monochloroacetic acid; unsaturated fatty acids, such as acrylic acid, crotonic acid, and oleic acid; aromatic carboxylic acids, such as benzoic acid, phthalic acid, and salicylic acid; dicarboxylic acids, such as maleic acid and fumaric acid; and sulfonic acids, such as methanesulfonic acid and paratoluenesulfonic acid; and inorganic acids, such as hydrochloric acid, sulfuric acid, sulfurous acid, nitric acid, nitrous acid, and phosphoric acid. Examples of hydrogen salts include sodium hydrogen sulfide, disodium hydrogen phosphate, sodium hydrogen carbonate, etc. However, in practical use, organic acids are preferred because they are less corrosive to metal members. In the above methods (1) to (5), the PAS resin (A) may be dried in vacuum, in air, or in an atmosphere of an inert gas such as nitrogen.
[0040] In particular, the PAS resin (A) post-treated by the above method (4) has an increased amount of acid groups bonded to its molecular terminals, and when mixed with polyphenylene ether resin, fluororesin, or modified elastomer (C), it has the effect of increasing the dispersibility of these resins. The acid group is preferably a carboxyl group. If the content of the PAS resin (A) is within the above range, the film can be imparted with the inherent heat resistance and chemical resistance of the PAS resin, and the stretchability can be maintained. In the present invention, the term "main component" means that the specific resin is contained in an amount of 50% by mass or more, preferably 60% by mass or more, based on the total mass of the resin components used to form the resin composition.
[0041] In order for the PAS resin to exhibit heat resistance, it is preferable that the melting point does not fall below 275°C.
[0042] [Thermoplastic resin other than polyarylene sulfide resin (B)] The thermoplastic resin (B) other than the polyarylene sulfide resin of the present invention (hereinafter, sometimes referred to as "thermoplastic resin (B)") may be a thermoplastic resin having a glass transition temperature of 200°C or higher or a melting point of 230°C or higher. For example, various polymers such as polyphenylene ether, polyethersulfone, polyphenylsulfone, polyetherimide, polysulfone, fluorine-based resin, and blends containing at least one of these polymers can be used. Among them, polyphenylene ether or fluorine-based resin is preferred from the viewpoints of low dielectric properties, mixability with PAS-based resin, adhesion to epoxy glass cloth substrate, and low moisture absorption.
[0043] [Polyphenylene ether resin (PPE resin) (B1)] Since polyphenylene ether resin (PPE resin) is an amorphous resin, it softens below the melting point of PAS resin if it is above its glass transition temperature. Therefore, when bonding copper foil at high temperatures below the melting point of PAS resin or performing annealing treatment, a resin composition in which amorphous PPE resin is dispersed can conform to the copper foil unevenness better than a crystalline polymer PAS resin alone, and can improve the adhesive strength between the resin and copper foil. In addition, since PPE resin has a low dielectric tangent, it is easier to obtain physical properties suitable for high frequency applications than polymers with poor dielectric tangents such as polycarbonate. In addition, since PPE resin has aromatic rings and oxygen-containing functional groups, it has the characteristic of having better adhesiveness than aliphatic hydrocarbons such as polypropylene (PP).
[0044] The PPE resin is a homopolymer and / or copolymer having a structural portion represented by the following structural formula (9).
[0045] [ka]
[0046] In the above formula, each R2 is independently a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a haloalkyl group, an aminoalkyl group, a hydrocarbyloxy group, or a halohydrocarbyloxy group in which at least two carbon atoms separate the halogen atom from the oxygen atom, and each m is independently an integer of 1 to 4.
[0047] Specific examples of PPE resins include poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), and further include polyphenylene ether copolymers such as copolymers of 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol and 2-methyl-6-butylphenol). Among these, poly(2,6-dimethyl-1,4-phenylene ether) and copolymers of 2,6-dimethylphenol and 2,3,6-trimethylphenol are preferred, and poly(2,6-dimethyl-1,4-phenylene ether) is more preferred.
[0048] The content of the PPE resin is preferably 3 to 49 mass % based on the total amount of organic components in the resin composition, more preferably 5 to 40 mass % from the viewpoint of uniform dispersion in the composition, and even more preferably 10 to 35 mass % for even more uniform dispersion.
[0049] The number average molecular weight of the PPE resin is preferably 1,000 or more, more preferably 1,500 to 50,000, and even more preferably 500 to 30,000.
[0050] [Fluorine resin (B2)] Fluorine-based resins have properties suitable for use as insulating substrates for high frequencies, such as low dielectric tangent and low water absorption. Furthermore, when dispersed in a PAS-based resin, their flexibility enhances the ability of the PAS-based resin to conform to the unevenness of the metal layer or the epoxy glass cloth laminate, thereby improving adhesion strength. The structure of the fluorine-based resin (B2) is not particularly limited, but is composed of at least one type of fluoroolefin unit. Examples include tetrafluoroethylene polymers, copolymers with perfluoro(alkyl vinyl ether), hexafluoropropylene, vinylidene fluoride, vinyl fluoride, trifluoroethylene, and chlorotrifluoroethylene, and further copolymers with non-fluorine-containing ethylene monomers such as ethylene, propylene, butene, and alkyl vinyl ethers. Specific examples include polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene-hexafluoropropylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, etc. Among these, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, and tetrafluoroethylene-hexafluoropropylene copolymer are preferred from the viewpoint of ease of melt extrusion.
[0051] Among the fluorine-based resins (B2), fluorine-based resins (B2) having functional groups are preferred. The fluorine-based resins (B2) having functional groups have at least one reactive functional group selected from the group consisting of a carbonyl group-containing group, a hydroxy group, an epoxy group, and an isocyanate group. Two or more of these reactive functional groups may be included. Among them, the carbonyl group-containing group is preferred from the viewpoint of excellent reactivity with the PAS resin (A). Examples of the carbonyl group-containing group include a group having a carbonyl group between the carbon atoms of a hydrocarbon group, a carbonate group, a carboxy group, a haloformyl group, an alkoxycarbonyl group, an acid anhydride group, and a polyfluoroalkoxycarbonyl group.
[0052] Methods for introducing reactive functional groups into the fluororesin (B2) having functional groups include: (1) using a monomer having a reactive functional group when producing the main chain of the fluororesin having functional groups by polymerization reaction; (2) producing the fluororesin (B2) having functional groups by polymerization reaction using a chain transfer agent that generates a radical having a reactive functional group; (3) producing the fluororesin (B) having functional groups by polymerization reaction using a polymerization initiator that generates a radical having a reactive functional group; (4) modifying the fluororesin by a technique such as oxidation or thermal decomposition; and (5) blending a compound or resin that is compatible with the fluororesin and contains the functional group.
[0053] Examples of the reactive functional group-containing monomer include a monomer having a carbonyl group-containing group, an epoxy group-containing monomer, a hydroxy group-containing monomer, and an isocyanate group-containing monomer.
[0054] Examples of monomers having a carboxyl group-containing group include unsaturated dicarboxylic acids (maleic acid, itaconic acid, citraconic acid, crotonic acid, himic acid, 5-norbornene-2,3-dicarboxylic acid, maleic acid), their unsaturated dicarboxylic acid anhydrides, unsaturated monocarboxylic acids (acrylic acid, methacrylic acid), vinyl esters (vinyl acetate, vinyl chloroacetate, vinyl butanoate, vinyl pivalate, vinyl benzoate, vinyl crotonate), and the like.
[0055] Examples of the hydroxy group-containing monomer include hydroxy group-containing vinyl ester, hydroxy group-containing vinyl ether, hydroxy group-containing allyl ether, hydroxy group-containing (meth)acrylate, hydroxyethyl crotonate, and allyl alcohol.
[0056] Examples of the epoxy group-containing monomer include unsaturated glycidyl ethers (allyl glycidyl ether, 2-methylallyl glycidyl ether, vinyl glycidyl ether, etc.) and unsaturated glycidyl esters (glycidyl acrylate, glycidyl methacrylate, etc.).
[0057] Examples of the isocyanate group-containing monomer include 2-(meth)acryloyloxyethyl isocyanate, 2-(2-(meth)acryloyloxyethoxy)ethyl isocyanate, and 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate.
[0058] The amount of reactive functional groups contained in the fluororesin (B2) having a functional group is preferably 0.01 to 3 mol %, more preferably 0.03 to 2 mol %, and even more preferably 0.05 to 1 mol % of all units constituting the fluororesin (B2) having a functional group. If the amount of reactive functional groups is within the above range, the reactivity with the PAS resin is excellent and deterioration of the flowability can be suppressed.
[0059] The melting point of the fluororesin (B2) used in the present invention is not particularly limited, but is 230° C. to 320° C., preferably 250° C. to 310° C., and more preferably 260° C. to 300° C. If the melting point of the fluororesin (B2) is within the above range, heat resistance can be maintained and good melt extrusion stability can be obtained.
[0060] The glass transition temperature of the fluororesin (B2) used in the present invention is not particularly limited, but is 110° C. or less, and more preferably 100° C. or less. If the fluororesin (B2) has the above glass transition temperature, in the stretching after mixing with the PAS resin (A), the dispersed phase of the fluororesin (B2) is also stretched at the stretching temperature of the PAS resin (A), so that peeling at the interface between the continuous phase PAS resin (A) and the dispersed phase fluororesin (B2) can be suppressed. As a result, breakage during stretching can be suppressed, and further, a film having excellent mechanical properties can be obtained.
[0061] The content of the fluororesin (B2) in the resin composition is preferably 3 to 49% by mass, more preferably 5 to 40% by mass from the viewpoint of uniform dispersion in the composition, and even more preferably 10 to 35% by mass for even more uniform dispersion. If the content of the fluororesin (B2) is within the above range, the effect of improving the dielectric properties (lowering the dielectric constant) of the film is more significantly exhibited.
[0062] In the present invention, it is also possible to use a fluorine-based resin (B2) in combination with the PPE-based resin (B1).
[0063] [Modified elastomer (C)] The modified elastomer (C) is a component that has a reactive group capable of reacting with at least one of the PAS resin (A), the PPE resin (B1), and the fluorine-based resin (B2), and thus has the function of improving the mechanical strength (such as folding endurance) of the insulating layer. The reactive group of the modified elastomer (C) is preferably at least one selected from the group consisting of an epoxy group and an acid anhydride group, and more preferably an epoxy group, which can rapidly react with the functional groups at the molecular terminals of the PAS resin (A), the PPE resin (B1), and the fluorine resin (B2).
[0064] Examples of such modified elastomers (C) include copolymers containing repeating units based on an α-olefin and repeating units based on a vinyl polymerizable compound having the above-mentioned functional group, and copolymers containing repeating units based on an α-olefin, repeating units based on a vinyl polymerizable compound having the above-mentioned functional group, and repeating units based on an acrylic ester.
[0065] Examples of the α-olefin include α-olefins having 2 to 8 carbon atoms, such as ethylene, propylene, and butene-1. Examples of the vinyl polymerizable compound having a functional group include α,β-unsaturated carboxylic acids and esters thereof, such as acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters; α,β-unsaturated dicarboxylic acids and esters thereof, such as maleic acid, fumaric acid, itaconic acid, and other unsaturated dicarboxylic acids having 4 to 10 carbon atoms, mono- or diesters thereof, and acid anhydrides thereof; α,β-unsaturated dicarboxylic acids, esters thereof, and acid anhydrides thereof; and α,β-unsaturated glycidyl esters.
[0066] The α,β-unsaturated glycidyl ester is not particularly limited, but examples thereof include a compound represented by the following formula (10).
[0067] [ka]
[0068] In the above formula, R 3 is an alkenyl group having 1 to 6 carbon atoms. Examples of the alkenyl group having 1 to 6 carbon atoms include a vinyl group, a 1-propenyl group, a 2-propenyl group, a 1-methylethenyl group, a 1-butenyl group, a 2-butenyl group, a 1-methyl-1-propenyl group, a 1-methyl-2-propenyl group, a 2-methyl-1-propenyl group, a 2-methyl-2-propenyl group, a 1-pentenyl group, a 2-pentenyl group, a 3-pentenyl group, a 4-pentenyl group, a 1-methyl-1-pentenyl group, a 1-methyl-3-pentenyl group, a 1,1-dimethyl-1-butenyl group, a 1-hexenyl group, and a 3-hexenyl group.
[0069] R 4 are each independently a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a pentyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 2,2-dimethylpropyl group, a hexyl group, a 1-methylpentyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 4-methylpentyl group, a 2,2-dimethylbutyl group, a 2,3-dimethylbutyl group, a 2,4-dimethylbutyl group, a 3,3-dimethylbutyl group, and a 2-ethylbutyl group.
[0070] Specific examples of the α,β-unsaturated glycidyl ester include glycidyl acrylate and glycidyl methacrylate, with glycidyl methacrylate being preferred. The proportion of repeating units based on α-olefin in the modified elastomer (C) is preferably 50 to 95 mass%, more preferably 50 to 80 mass%. When the proportion of repeating units based on α-olefin is within the above range, the stretching uniformity and folding strength of the film can be improved. The proportion of the repeating units based on the vinyl polymerizable compound having a functional group in the modified elastomer (C) is preferably 1 to 30 mass%, more preferably 2 to 20 mass%. When the proportion of the repeating units based on the vinyl polymerizable compound having a functional group is within the above range, not only the desired improvement effect but also good extrusion stability can be obtained.
[0071] The content of the modified elastomer (C) in the resin composition is preferably 1 to 15 mass %, more preferably 3 to 10 mass %. When the content of the modified elastomer (C) is within the above range, the effect of improving the folding endurance and the like is significantly exhibited.
[0072] [Silane coupling agents] In the present invention, it is preferable to use a silane coupling agent as a component having a function of increasing the affinity (interaction) between the PAS resin (A) and other components (the PPE resin (B1), the fluorine-based resin (B2), and the modified elastomer (C)). This dramatically improves the dispersibility of the other components in the PAS resin (A), enabling the formation of a good morphology.
[0073] The silane coupling agent is preferably a compound having a functional group capable of reacting with a carboxyl group. The silane coupling agent reacts with any of the PAS resin (A), the PPE resin (B1), the fluorine resin (B2), and the modified elastomer (C) to form a strong bond therewith. As a result, the effect of the silane coupling agent is more pronounced, and the dispersibility of the PPE resin (B1), the fluorine resin (B2), and the modified elastomer (C) in the PAS resin (A) can be particularly improved.
[0074] Examples of such silane coupling agents include compounds having an epoxy group, an isocyanate group, or an amino group. Specific examples of the silane coupling agent include epoxy group-containing alkoxysilane compounds such as γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; isocyanato group-containing alkoxysilane compounds such as γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyldimethoxysilane, γ-isocyanatopropylethyldiethoxysilane, and γ-isocyanatopropyltrichlorosilane; amino group-containing alkoxysilane compounds such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane; and hydroxyl group-containing alkoxysilane compounds such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane.
[0075] The content of the silane coupling agent in the resin composition is preferably 0.1 to 5 mass%, more preferably 0.2 to 2.5 mass%. When the content of the silane coupling agent is within the above range, the effect of improving the dispersibility of other components in the PAS resin (A) is significantly exhibited.
[0076] [Additives] The resin composition may contain a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, an ultraviolet stabilizer, a lubricant, an antistatic agent, and a colorant, so long as the effects of the present invention are not impaired.
[0077] [Low dielectric materials (resin compositions and films)] <Method of producing resin composition> The method for producing the resin composition is not particularly limited, but includes a method in which the PAS resin (A), the thermoplastic resin (B), and other components (modified elastomer (C), silane coupling agent) are mixed uniformly using a tumbler mixer or a Henschel mixer, and then the mixture is fed into a twin-screw extruder for melt-kneading. This melt-kneading may be either kneading in a shear flow field or kneading in an extensional flow field, or both. This melt-kneading is preferably performed under conditions in which the ratio of the discharge rate (kg / hr) of the kneaded product to the screw rotation speed (rpm) (discharge rate / screw rotation speed) is 0.02 to 0.2 (kg / hr rpm).
[0078] The set temperature during mixing is selected within a range of +5 to +70° C. from the melting point of the PAS resin (A) or the thermoplastic resin (B), whichever has the higher melting point, and is more preferably within a range of +10 to +50° C. If the set temperature is lower than the melting points of the PAS resin (A) and the thermoplastic resin (B), the viscosity of the composition increases significantly due to the presence of the partially unmelted PAS resin (A) or the thermoplastic resin (B), which increases the load on the twin-screw extruder, which is undesirable from the viewpoint of productivity. More specifically, it is preferable to feed each component into a twin-screw extruder and melt-knead it under temperature conditions of about 310°C resin temperature in the strand die at the above-mentioned set temperature. In this case, the discharge rate of the kneaded product is in the range of 5 to 50 kg / hr at a rotation speed of 250 rpm. In particular, from the viewpoint of enhancing the dispersibility of each component, it is preferable that the discharge rate of the kneaded product is 20 to 35 kg / hr at a rotation speed of 250 rpm. Therefore, it is more preferable that the ratio of the discharge rate (kg / hr) of the kneaded product to the screw rotation speed (rpm) (discharge rate / screw rotation speed) is 0.08 to 0.14 (kg / hr rpm).
[0079] <Film> The insulating layer of the printed wiring board (2) of the present invention can be formed by a PAS film produced from the above-mentioned resin composition. In one embodiment of such a PAS film, the PAS resin (A) serves as a matrix (continuous phase), and particles (dispersed phase) containing a PPE resin (B1) and a fluorine-based resin (B2) are dispersed in the matrix.
[0080] The present inventors also believe that the modified elastomer (C) also functions as a compatibilizer for the PAS resin (A), the PPE resin (B1) and the fluororesin (B2), thereby finely dispersing the particles in the matrix, thereby improving the mechanical strength of the film. Furthermore, the present inventors also believe that the combined use of the modified elastomer (C) with a silane coupling agent further improves the adhesiveness at the interface between the matrix and the particles via the modified elastomer (C), thereby further improving the mechanical strength of the film.
[0081] The film is preferably a biaxially stretched film obtained by biaxially stretching a sheet obtained from a resin composition. When the film is a biaxially stretched film, the PAS resin (A) constituting the matrix crystallizes in a state in which its molecular chain is stretched, so that a film with high dimensional accuracy can be obtained. However, if it is necessary to reduce costs, a non-stretched film that requires fewer steps can also be selected.
[0082] The stretching ratio in the longitudinal direction (MD direction) of the biaxially stretched film is preferably 1.5 to 4 times, and more preferably 2.0 to 3.8 times. The stretching ratio in the width direction (TD) of the biaxially stretched film is preferably 1.5 to 4 times, and more preferably 2.0 to 3.8 times. The ratio of the stretching ratio in the width direction (TD direction) of the biaxially stretched film to the stretching ratio in the longitudinal direction (MD direction) of the biaxially stretched film (width direction (TD direction) / longitudinal direction (MD direction)) is preferably 0.8 to 1.3, and more preferably 0.9 to 1.2 because this makes it easier to balance the physical properties in the longitudinal direction and the physical properties in the width direction.
[0083] <Method of manufacturing biaxially stretched film> The biaxially stretched film is produced, for example, as follows. First, the resin composition is dried at 140°C for 3 hours or more, and then charged into an extruder heated to 280 to 320°C. Thereafter, the molten resin composition (i.e., the kneaded product) that has passed through the extruder is extruded into a sheet (film) from a T-die. Next, the sheet-like kneaded product is cooled and solidified by being brought into close contact with a cooling roll having a surface temperature of 20 to 50° C. In this way, an unstretched sheet in a non-oriented state is obtained.
[0084] Next, the unstretched sheet is biaxially stretched by a sequential biaxial stretching method, a simultaneous biaxial stretching method, or a combination of these methods. When biaxial stretching is performed by the sequential biaxial stretching method, for example, the obtained unstretched sheet is heated with a group of heating rolls and stretched in the longitudinal direction (MD direction) by 1.5 to 4 times (preferably 2.0 to 3.8 times) in one stage or in two or more stages, and then cooled with a group of cooling rolls at 30 to 60°C. The stretching temperature is preferably from the glass transition temperature (Tg) of the PAS resin (A) to Tg+40°C, more preferably from Tg+5°C to Tg+30°C, and even more preferably from Tg+5°C to Tg+20°C.
[0085] Next, the film is stretched in the transverse direction (TD) by using a tenter. Both ends of the film stretched in the MD are held by clips and introduced into the tenter, where it is stretched in the TD. The stretching ratio is preferably 1.5 to 4 times, and more preferably 2.0 to 3.8 times. The stretching temperature is preferably from Tg to Tg+40°C, more preferably from Tg+5°C to Tg+30°C, and further preferably from Tg+5°C to Tg+20°C.
[0086] The stretched film is then heat set while under tension or relaxed in the width direction. The heat setting temperature is not particularly limited, but is preferably 200 to 280°C, more preferably 220 to 280°C, and even more preferably 240 to 275°C. The heat setting may be carried out in two stages by changing the heat setting temperature. In this case, it is preferable that the heat setting temperature in the second stage is higher by +10 to 40°C than the heat setting temperature in the first stage. A stretched film heat set at a heat setting temperature in this range has improved heat resistance and mechanical strength. The heat setting time is preferably 1 to 60 seconds.
[0087] Furthermore, this film is cooled while being relaxed in the width direction in a temperature zone of 50 to 270° C. The relaxation rate is preferably 0.5 to 10%, more preferably 2 to 8%, and further preferably 3 to 7%.
[0088] In order to improve the thermal stability of the film, a heat treatment (annealing treatment) may be further performed. Examples of heat treatment methods after stretching include known methods such as a method of blowing hot air, a method of irradiating infrared rays, and a method of irradiating microwaves. Among them, a method of blowing hot air is preferable because it can heat uniformly and accurately. The heat treatment temperature is preferably 150 to 260°C, and more preferably 160 to 240°C. If the above heat treatment is not performed, it is difficult to relax the stress of the film, and a heat treatment at a temperature of 150°C or less cannot sufficiently relax the stress, and the thermal shrinkage rate of the film after production cannot be reduced. As a result, it is difficult to improve the thermal stability of the film. In addition, if the heat treatment temperature is 260°C or more, melting of a part of the crystalline phase of polyphenylene sulfide progresses, and the orientation is broken. Therefore, the linear expansion coefficient in the plane direction of the film after production is deteriorated. As a result, it is difficult to improve the thermal stability of the film. The heat treatment time is preferably 3 to 300 seconds, and more preferably 5 to 100 seconds.
[0089] [High frequency hybrid substrate] The high-frequency hybrid substrate of the present invention can be manufactured by laminating a printed wiring board (2) having an insulating layer of a PAS-based film on a printed wiring board (1) having an insulating layer formed of an epoxy glass cloth laminate. Alternatively, it can be manufactured by laminating a copper-clad PAS-based film on the printed wiring board (1) and then forming wiring on the outermost copper layer by a known method. Alternatively, it can be manufactured by laminating a PAS-based film and a metal layer on the printed wiring board (1) in order or simultaneously, and forming wiring on the outermost layer by a known method. A known method can be selected for attaching each of the above-mentioned materials to the printed wiring board (1). For example, it can be manufactured by direct lamination by hot pressing utilizing the thermoplasticity of the PAS-based film, or lamination using an adhesive, a bonding sheet, or a prepreg. Furthermore, a printed circuit board can be obtained by connecting electronic components to operate as an electronic circuit.
[0090] [Millimeter wave radar, antenna] The high frequency hybrid substrate of the present invention is ideal as a substrate for millimeter wave radar and antennas used at high frequencies, and has the advantage of enabling miniaturization and faster communication speeds due to low transmission loss when used as an antenna for in-vehicle millimeter wave radar and 5G smartphones. EXAMPLES
[0091] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these.
[0092] [Example 1] A mixture was obtained by uniformly mixing 80 parts by mass of a PAS resin (A) (linear polyphenylene sulfide, manufactured by DIC Corporation) and 20 parts by mass of a polyphenylene ether resin (PPE resin) (B1), PX-100 (manufactured by Mitsubishi Engineering Plastics Corporation), in a tumbler mixer.
[0093] The mixture obtained above was then fed into a vented twin-screw extruder "TEX-30α" manufactured by Japan Steel Works, Ltd. The mixture was melt extruded and discharged in the form of strands under conditions of a discharge rate of 20 kg / hr, a screw rotation speed of 300 rpm, and a set temperature of 300°C, and then cooled with water at a temperature of 30°C, followed by cutting to produce a resin composition.
[0094] The average particle size of the particles in the produced resin composition was measured as follows. First, the resin composition pellets were cut perpendicular to the flow direction by ultra-thin sectioning. Next, the cut surfaces of the cut pellets were photographed with a scanning electron microscope (SEM) at 2000 times magnification, and the obtained images were enlarged to A3 size. Next, 50 particles were selected randomly from the enlarged SEM photographs, and the maximum diameter of each particle on the cut surface was measured to calculate the average particle size. As a result, the average particle size of the particles in the resin composition pellets was 0.9 μm.
[0095] In addition, the resin pellets made of the resin composition obtained above were subjected to SEM-EDS analysis to analyze the components constituting the matrix and particles of the resin composition pellets. As a result, it was found that the component constituting the matrix was a PAS-based resin, and the component constituting the particles was a PPE resin.
[0096] Next, this resin composition was dried at 140° C. for 3 hours, and then charged into a full-flight screw single-screw extruder and melted under conditions of 280 to 310° C. The molten resin composition was extruded from a T-die and then cooled in close contact with a chill roll set at 40° C. to produce an unstretched sheet.
[0097] Next, the unstretched sheet was biaxially stretched 3.0x3.0 times at 100°C using a batch-type biaxial stretching machine (manufactured by Imoto Manufacturing Co., Ltd.) to obtain a film with a thickness of 50 μm. The obtained film was then fixed to a mold and heat-set in an oven at 275°C to produce a biaxially stretched film.
[0098] A 12 μm thick copper layer was formed on the obtained biaxially stretched film by double-sided sputter plating to obtain a copper-clad laminate. A wiring pattern was further formed on the copper layer by resist etching to obtain a printed wiring board (2).
[0099] Next, a wiring pattern was created by resist etching on an epoxy glass cloth laminate (manufactured by Sanhayato, substrate thickness 1.6 mm, copper foil thickness 18 μm) with copper foil attached to both sides, to obtain a printed wiring board (1). A high-frequency hybrid substrate was manufactured by stacking the printed wiring board (1), glass cloth substrate / epoxy resin prepreg (manufactured by Risho Kogyo Co., Ltd., substrate thickness 0.18 mm), and the above printed wiring board (2) in that order and subjecting them to heat treatment in a vacuum press. The prepreg has the effect of bonding the upper and lower surfaces together through heat treatment, and becomes an epoxy glass cloth layer after hardening.
[0100] [Example 2] A high-frequency hybrid substrate was manufactured in the same manner as in Example 1, except that a printed wiring board (2) having an insulating layer made of a resin composition consisting of 80 parts by mass of PAS-based resin (A), 10 parts by mass of PX-100 (B1), and 10 parts by mass of EA-2000 (manufactured by AGC Corporation, melting point 300°C) (B2), was used, and the printed wiring board (2) was laminated on both sides of the printed wiring board (1) via a glass cloth base material / epoxy resin prepreg.
[0101] [Example 3] A high frequency hybrid substrate was produced in the same manner as in Example 1, except that the PAS resin (A) was 70 parts by mass, the PX-100 (B1) was 20 parts by mass, and the EA-2000 (B2) was 10 parts by mass.
[0102] [Example 4] A high frequency hybrid substrate was produced in the same manner as in Example 1, except that the PAS resin (A) was 60 parts by mass, the PX-100 (B1) was 10 parts by mass, and the EA-2000 (B2) was 30 parts by mass, and the high frequency single-sided copper-clad laminate and the printed wiring board (1) were laminated with a bonding sheet.
[0103] [Example 5] A high frequency hybrid substrate was manufactured in the same manner as in Example 1, except that the components were 67 parts by mass of PAS resin (A), 20 parts by mass of PX-100 (B1), 10 parts by mass of EA-2000 (B2), and 3% by mass of Bondfast 7L (manufactured by Sumitomo Chemical Co., Ltd., ethylene / glycidyl methacrylate / methyl acrylate=70 / 3 / 27 (mass%), hereinafter sometimes referred to as "BF7L"), which is the modified elastomer (C).
[0104] [Example 6] A high frequency hybrid substrate was produced in the same manner as in Example 1, except that 80 parts by mass of the PAS resin (A), 20 parts by mass of PX-100 (manufactured by Mitsubishi Engineering Plastics Corporation), and 0.3 parts by mass of the silane coupling agent were uniformly mixed in a tumbler mixer.
[0105] [Example 7] A high frequency hybrid substrate was produced in the same manner as in Example 1, except that a polyphenylsulfone resin (B3) (manufactured by BASF Ltd., glass transition temperature 220°C, hereinafter sometimes referred to as "PPSU") was used as the thermoplastic resin (B).
[0106] [Example 8] A high frequency hybrid substrate was produced in the same manner as in Example 1, except that a polysulfone resin (B4) (manufactured by SOLVAY Corporation, glass transition temperature 190° C., hereinafter sometimes referred to as “PSU”) was used as the thermoplastic resin (B).
[0107] Comparative Example 1 A high frequency hybrid substrate was produced in the same manner as in Example 1, except that 50 parts by mass of the PAS resin (A) and 50 parts by mass of PX-100 (B1) were used.
[0108] Comparative Example 2 A high frequency hybrid substrate was produced in the same manner as in Example 1, except that 100 parts by mass of the PAS resin (A) was used and PX-100 was not used.
[0109] Comparative Example 3 A high frequency hybrid substrate was produced in the same manner as in Example 1, except that the PAS film was changed to a film of 100 parts by mass of normal polyimide (manufactured by Toray DuPont, thickness 50 μm).
[0110] 2. Evaluation 2-1. Stretching Thirty unstretched sheets of PAS resin were biaxially stretched, and the success rate of obtaining a stretched film without breaking was evaluated. [Evaluation Criteria] ◎: 90% or more 〇: 70% or more ×: Less than 70%
[0111] 2-2. Dielectric constant and dielectric tangent The dielectric constant was measured based on the cavity resonance method specified in JIS C 2565:1992. Specifically, a strip of 2 mm wide x 150 mm long was prepared from a PAS film or polyimide film. The prepared strip was then left to stand for 24 hours in an environment of 23°C and 50% Rh, and the dielectric constant at a frequency of 1 GHz was measured by the cavity resonance method using ADMS010c series (manufactured by AET Corporation). A dielectric constant of 3.2 or less was marked as ◎, a dielectric constant of 3.4 or less was marked as ◯, and a dielectric constant greater than 3.4 was marked as ×. A dielectric loss tangent of 0.003 or less was marked as ◎, a dielectric loss tangent of 0.004 or less was marked as ◯, and a dielectric loss tangent of more than 0.004 was marked as ×.
[0112] 2-3. Metal adhesion The metal adhesion was evaluated according to the following criteria by measuring the peel strength between the metal layer and the PAS film or polyimide film in accordance with the test method specified in JIS K 6854:1999. ◎:5N / cm or more ○: 4N / cm or more and less than 5N / cm ×: Less than 4N / cm
[0113] 2-4.Flame retardancy Flame retardancy was evaluated using five test pieces measuring 200mm x 50mm each based on the UL94 VTM-0 (vertical flame test for thin plastic materials) standard. Flame retardancy was rated as ◯ if it was VTM-0, and ◯ otherwise. Here, VTM-0 is based on the following conditions: the burning time after the first flame contact (hereafter abbreviated as t1) and the burning time after the second flame contact (hereafter abbreviated as t2) of each sample are both 10 seconds or less, t1+t2 of all five samples are 50 seconds or less, the sum of t2 and afterglow time (time the sample burns red without emitting flame) of each sample after the second flame contact is 30 seconds or less, there is no afterglow or afterglow up to the holding clamp of each sample, and there is no ignition of the cotton for marking by the flaming material or dripping.
[0114] 2-5. Adhesion to the insulating layer formed by epoxy glass cloth laminate The epoxy glass cloth adhesion was evaluated by measuring the peel strength after bonding an epoxy glass cloth laminate and a PAS film with a prepreg by hot pressing at 150°C for 1 hour, and according to the following criteria. ◎:5N / cm or more ○: 4N / cm or more and less than 5N / cm ×: Less than 4N / cm
[0115] 2-6.Low warpage When a 10 cm square high frequency hybrid substrate was formed, if the warping at all four corners was less than 1.0 mm, it was rated as ◯, and otherwise as ×.
[0116] 2-7.Transmission loss A microstrip line was created using a high-frequency hybrid substrate, and a network analyzer (Keysight Technologies) was used to evaluate the transmission loss at 50GHz using the probe method. Less than -8.0dB / 100mm was marked as ◎, less than -9.0dB / 100mm as 〇, and more than that as ×.
[0117] 2-8. Reflow resistance The obtained high frequency hybrid substrate was heat-treated in a hot air dryer at 260°C for 30 minutes, and then the PAS-based film was rated as ◯ if no deformation such as waviness or swelling or peeling occurred, and x if the PAS-based film showed deformation such as waviness or swelling.
[0118] The above results are summarized in Tables 1 to 3.
[0119] [Table 1] *PAS: Polyarylene sulfide resin PPE; Polyphenylene ether resin PPSU; Polyphenylsulfone resin PSU; Polysulfone resin
[0120] [Table 2]
[0121]
Table 3
Claims
1. A high-frequency hybrid substrate in which a printed wiring board (2) having an insulating layer made of a low-dielectric material is laminated on one or both sides of a printed wiring board (1) having an insulating layer formed of an epoxy glass cloth laminate, A high frequency hybrid substrate, characterized in that the low dielectric material is made of a resin composition of a polyarylene sulfide resin (A) and a thermoplastic resin (B) other than a polyarylene sulfide resin having a glass transition temperature of 200°C or higher or a melting point of 230°C or higher.
2. 2. The high frequency hybrid substrate according to claim 1, wherein the blending ratio of the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher is in the range of 3 to 49 mass% relative to 100 mass% of the total amount of the polyarylene sulfide resin (A) and the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher.
3. 3. The high frequency hybrid substrate according to claim 1, wherein the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 200° C. or higher or a melting point of 230° C. or higher is a dispersed phase having an average dispersed diameter of 5 μm or less.
4. 3. The high frequency hybrid substrate according to claim 1, wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is at least one selected from the group consisting of polyphenylene ether resin, polyethersulfone resin, polyphenylsulfone resin, polyetherimide resin, polysulfone resin, and fluorine-based resin.
5. 3. The high frequency hybrid substrate according to claim 1, wherein the dielectric constant of the low dielectric material is 3.4 or less.
6. 3. The high frequency hybrid substrate according to claim 1, further comprising a modified elastomer (C) having a reactive group added to a resin composition of a low dielectric material.
7. 7. The high frequency hybrid substrate according to claim 6, wherein the modified elastomer (C) comprises an olefin polymer having at least a functional group selected from the group consisting of an epoxy group and an acid anhydride group.
8. The high frequency hybrid substrate according to claim 6, wherein the blending ratio of the modified elastomer (C) is 1 to 15 mass% relative to 100 mass% in total of the polyarylene sulfide resin (A), the thermoplastic resin (B), and the modified elastomer (C).
9. 7. The high frequency hybrid substrate according to claim 6, wherein the modified elastomer (C) has an α-olefin content of 50 to 95% by mass based on the total mass of the modified elastomer.
10. The high frequency hybrid substrate according to claim 6, further comprising 0.01 to 5 mass % of a silane coupling agent (D) having at least one functional group selected from an epoxy group, an amino group, and an isocyanate group.
11. A millimeter wave radar and antenna using the high frequency hybrid substrate according to claim 1 or 2.
Citation Information
Patent Citations
Multilayered printed wiring board
JP1994005998A
Multilayer printed wiring board
JP2016040797A
Multilayer circuit board
JP2020174115A